Trajectories of asthma symptom presenting as wheezing and their associations with family environmental factors among children in Australia: evidence from a national birth cohort study. Issue 6 (6th June 2022) - Shahunja, K M; Sly, Peter D; Chisti, Md Jobayer; Mamun, Abdullah
Abstract : Objectives: Asthma is one of the greatest health burdens, yet contributors to asthma symptom trajectories are understudied in Australian children. We aimed to assess the trajectories of asthma symptom and their associations with several family environmental factors during the childhood period in Australia. Design: Secondary analysis from a cross-sequential cohort study. Setting: Nationwide representative data from the 'Longitudinal Study of Australian Children (LSAC)'. Participants: Participants from the LSAC birth cohort. Outcome measures: Asthma symptom trajectory groups. Methods: Asthma symptom presenting as wheezing, family environmental factors and sociodemographic data (2004–2018) were obtained from the LSAC. Group-based trajectory modelling was applied to identify asthma symptom trajectories and multivariable logistic regression models were used to assess the associations between these and environmental factors. Results: Of 5107 children in the LSAC cohort, 3846 were included in our final analysis. We identified three distinct asthma symptom trajectories from age 0/1 year to 14/15 years: 'low/no' (69%), 'transient high' (17%) and 'persistent high' (14%). Compared with the 'low/no' group, children exposed to 'moderate and declining' (relative risk ratio (RRR): 2.22, 95% CI 1.94 to 2.54; RRR: 1.26, 95% CI 1.08 to 1.46) and 'high and persistent' prevalence of maternal smoking (RRR: 1.41, 95% CI 1.23 to 1.60; RRR: 1.26, 95% CI 1.10 to 1.44) were at increased risk of being classified into the 'transient high' and 'persistent high' trajectories of asthma symptom. Persistently bad external dwelling conditions (RRR: 1.27, 95% CI 1.07 to 1.51) were associated with 'transient high' trajectory while 'moderate and increasing' conditions of cluttered homes (RRR: 1.37, 95% CI 1.20 to 1.56) were associated with 'persistent high' trajectory of asthma symptom. Exposure to tobacco smoke inside the house also increased the risk of being in the 'persistent high' trajectory group (RRR: 1.30, 95% CI 1.12 to 1.50). Conclusion: Poor home environment increased the risk of asthma symptom during childhood. Improving home environment and reducing exposure to tobacco smoke may facilitate a favourable asthma symptom trajectory during childhood.